Dynamic interaction between the shaking table and the specimen during earthquake tests - Bairrão, R. (2009)
The boundary conditions between the tested structures and the platform of a large shaking table are a major parameter for the design and numerical analyses of shaking table tests. A foremost attention is given to the design of the foundation and anchorage of the structure. All analyses are made considering a completely rigid shaking table: rigid actuators and rigid platform. However, since quite a long time, the shaking table / structure interaction has been clearly observed (Blondet and Esparza, 1988) when analysing the shaking table / actuators interaction, depending on the control tuning. In CEA Saclay, during the last 15 years, decreases of mock-up frequencies between calculations and experimental tests of massive structures have been observed: CASSBA, CAMUS 1 to 4, CAMUS 2000 (Combescure and Ragueneau, 2002) and more recently SMART. For a long time it has been calculated, after tests, the global stiffness that the “Azalée” shaking table should have to explain those decreases. This paper describes and validates the finite-element model of this shaking table platform, presents the mock-up used and finally deals with and concludes on the shaking table / mock-up interaction.